The Linear Assignment Method for Ranking of Organizations with Service Quality Approach: A Case Study of Hotels in City of Isfahan - Hadi Shirouyehzad (Journal of Applied Research on Industrial Engineering, 2016)
One of the most important issues in modern societies is to provide better services and evaluation of provided services. Service organizations are always looking to increase their level of customer satisfaction. In this context, Service quality and service quality gaps analysis are taken into account. In this paper a method developed for ranking service organization based on the services quality approach and multi attribute decision making tools. In this method, options are organizations and the indicators are service quality gaps. However, other than gaps the perception of service quality is considered as a separate indicator. The weight of indicators are calculated by paired comparisons tools and experts panel results. Linear assignment method is used to rank the options. The developed method is used to rank seven hotels in city of Isfahan. The results show that the implemented method ranked the Abbasi hotel as first and Kosar hotel as last in the ranking.